Tinjauan Terhadap Faktor-Faktor Peningkatan Resiliensi Pada Remaja Akhir - Fardinand Azis Wiratmaja; Kemurnian Zega; King Kalbu Sarjannadil; Muhammad Galuh Hermawan; Muhammad Anharul Huda; Novan Nugroho; Wahyunnisa Aisy Agustini (Concept: Journal of Social Humanities and Education, 2023)
Late adolescents experience a critical phase of individual development with various challenges that can affect their mental and emotional well-being. The focus of this research is resilience, namely the ability to overcome, adapt and recover from stress or life pressure. The research aims to understand the factors that increase resilience in late adolescents, with a review of emotional regulation, impulse control, optimism, empathy, casual analysis, self-efficacy and achievement. This research uses a qualitative approach. Data was collected through interviews and observations with 7 late adolescent sources using random sampling. The research results show that the level of resilience of the majority of teenagers is in the good category. Factors such as optimism, self-efficacy, and impulse control play a key role in the formation of positive resilience. The conclusion of this research is that it emphasizes the importance of approaches in developing resilience in late adolescents. Empowerment efforts, particularly in emotional regulation and optimism, can help them face challenges, develop robust personal growth, and better prepare for the transition to adulthood. This research provides in-depth insights for the development of effective interventions to support the positive development of adolescents in their transition phase.